A MATLAB subset to C compiler targeting embedded systems - Bispo, João; Cardoso, João M. P. (Software, practice & experience, 2017)
Summary This paper describes MATISSE, a compiler able to translate a MATLAB subset to C targeting embedded systems. MATISSE uses LARA, an aspect‐oriented programming language, to specify additional information and transformations to the input MATLAB code, for example, insertion of code for initialization of variables, and specification of types and shapes of variables. The compiler is being developed bearing in mind flexibility, multitarget and multitoolchain support, allowing for the generation of several implementations in C from the same reference code in MATLAB. In this paper, we also present a number of techniques being employed in MATLAB to C compilation, such as element‐wise mapping operations, matrix views, weak types, and intrinsics. We validate these techniques using MATISSE and a set of representative benchmarks. More specifically, we evaluate the compiler with a set of 31 benchmarks using an embedded system board and a desktop computer. The results show speedups up to 1.8× by employing information provided by LARA aspects, when compared with C code generated without additional user information. When compared with the execution time of the original code running on MATLAB, the execution time of the generated C code achieved a geometric mean speedup of 13×. Copyright © 2016 John Wiley & Sons, Ltd.